A geografia da violência no município minerário de Parauapebas no período de 2007 a 2015 - PAIVA, João de Lima (Universidade Federal do Pará, 2017)
The final point of this assignment is to make a criminal diagnostic on Parauapebas city and erase the doubt of interference in the city's criminal production by the miner activity, and if it does, we need to know how: reducing, justifying or increasing the criminality. We know the city has one of the biggest miner reserves from Brazil and also the world, and a revenue from the greatest ones. This fact helps on decrease criminal activities which falls over its citizens. Also, if that revenue would distribute the capital goods and servicing inside of territory in a equanimity way or if it endures some of the same troubles that has been lived in other Para's cities. Therefore, a historic set up was made of economic and population data beyond countryside research. In the study's progress, rises an important and serious revelation and it is the likely reduction and a probably end to the reserve in mid-2035, fact that can intervene in the revenue's catchment. And considering this, the city is already working in economic and alternative ways for its population. So they shouldn't feel the impact from the revenue's decreasing, as a consequence, could increase the violence levels, which already is a dangerous reality today. This assignment analyse the criminality considering qualitative and measurable aspects from research data explained in historical and rational materialism also construction, which are connected in suburban's formation that turn into violence's producers and products. The central idea to be explained is, if the social and economic relationships in a city like Parauapebas can offer a better reality than ones that are proposed in other cities, or if nothing changes from some realities that has been lived in the country. The high city's revenue couldn't help in making a better life to the population. The violence levels, that's still too high, could be a reflection of a bad money distribution? With this omen of a likely reduction or and end to the miner reserve, what can we get from the city's criminal situation?